Pediatricians diagnosis in oral benign pathology of the newborn - Durán Gutiérrez Américo (Instituto Nacional de Pediatría, 2014)
Knowledge of oral pathology of the newborn is important for the pediatric odontologist and also for pediatricians in order to diagnose and adequately approach it. The newborn oral cavity has specific anatomical features which health care team must know how to identify benign oral conditions. The more common are: Bohn nod- ules, Epstein pearls, Fordyce granules, Riga Fede ulcer, eruption hematoma, candidiasis, herpes simplex, difficult dental eruption, lymphangioma, natal and neonatal teeth. For those teeth whether or no they have carried or worn edges should be pulled out if they affect oral function or if they are the cause of Riga Fede ulceration. Surgical treatment is also indicated for congenital epulis, mucocele, ranula and hemangioma. A successful treatment, is based on a good diagnosis and interdisciplinary treatment. This article briefly describes the most common oral conditions of newborns in order to orient the specialist (not the dentist) with practical recommendations for early and timely treatment.